A novel L1 retrotransposon marker for HeLa cell line identification. (April 2009) - Rahbari, Raheleh; Sheahan, Tom; Modes, Vasileios; Collier, Pam; Macfarlane, Catriona; Badge, Richard M.
The HeLa cell line is the oldest, most widely distributed, permanent human cell line. As a nearly ubiquitous inhabitant of laboratories using tissue culture techniques, its aggressive growth characteristics make it a problematic contaminant that can overgrow less robust cell lines. Consequently, HeLa contamination is common in both the research laboratory and cell line repository contexts, and its detection is hampered by the lack of a rapid, sensitive and robust assay. Here we report the development of a HeLa-specific DNA diagnostic test: a single duplex detection PCR assay targeting an L1 retrotransposon insertion. All HeLa clones from a geographically diverse panel were positive by this assay, and the particular L1 insertion we identified appears to be unique to the HeLa cell line. The assay can detect very low levels of HeLa contamination (<1%), and can be performed on un-purified cell pellets, allowing rapid routine screening.